Hull Structural Weight Estimation of New General Cargo Ships Using Principal Dimensions - Ahmad, Ghaleb (Latakia University Journal -Engineering Sciences Series, 2020)
The ship's lightweight is considered one of the main requirements of preliminary ship design. It's the most application parameter, which can be utilized starting from preliminary design phase all the way through the construction, until reaching the ship to the launching and delivery stage. Therefore, it's necessary a reliable estimation of weight to maintain a successful performance of ship. The weight is the major factor in determining the a adequacy of the ship stability before performing strength calculation. The accurate estimation of weight, plays the crucial role in determining the structural cost and competitive pricing. The ship's hull forms the main body of the ship. It's the most notable structural entity of the ship. It's the watertight enclosure of the ship, which protects the cargo, machinery and accommodation spaces of the ship from the weather, flooding, and structural damage. The weight of ship's hull forms from 50% to 80% of the lightweight for most of merchant ships. This research aims to determine the structural weight of new ships hull based on principal dimensions using simplified calculation method. يعتبر الوزن الفارغ للسفينة من المتطلبات الرئيسة للتصميم الأولي للسفن، وهو البارامتر الأكثر تطبيقا بدءا بمرحلة التصميم الأولي حتى الوصول بالسفينة الى مرحلة التسليم والتدشين. لذلك يجب تقدير الوزن بشكل موثوق للمحافظة على الأداء الجيد للسفينة، وتقديره التقريبي ذو أهمية كبيرة في تحقيق الاتزان للسفينة قبل اجراء حسابات المتانة، كما أنّ التقدير الدقيق للوزن هو المدخل الأكثر أهمية في تقدير التكلفة الانشائية والتسعير المنافس. يشكّل بدن السفينة الجسم الرئيس للسفينة، وهو الكيان الانشائي الأكثر أهمية في السفن، اذ يقوم بإحكام السفينة ضد الماء ويساهم في حماية السفينة من الغمر والعطب. يشكّل وزن البدن من 50% الى 80% من الوزن الفارغ لمعظم السفن التجارية. يهدف هذا البحث الى حساب الوزن الانشائي لبدن السفن الجديدة اعتمادا على الأبعاد الأساسية باستخدام طرق حسابية مبسطة.